Dechlorane plus monoadducts in a lake ontario (Canada) food web and biotransformation by lake trout (Salvelinus namaycush) liver microsomes. (19th April 2013) - Tomy, Gregg T.; Sverko, Ed; Palace, Vince; Rosenberg, Bruno; McCrindle, Robert; McAlees, Alan; Smith, Lindsay A.P.; Byer, Jonathan; Pacepavicius, Grazina; Alaee, Mehran; McCarry, Brian E.
Abstract Compounds related to the high‐production‐volume flame retardant Dechlorane Plus (DP) were measured in a Lake Ontario food web located downstream of a DP manufacturing plant. These compounds, 1, 3‐ and 1, 5‐DP‐monoadducts (DPMA), are positional isomers and are thought to arise from the incomplete reaction of DP or impurities in the DP starting material during its manufacture. The 1, 3‐DPMA isomer was measured (0.12–199 ng g−1 lipid wt) in all trophic levels, whereas 1, 5‐DPMA was measured only sporadically in the food web and was not detectable in the apex predator, lake trout (Salvelinus namaycush). Concentrations of DPMA isomers when detected in Lake Ontario biota were greater than that of total DP for all trophic levels. The prevalence of 1, 3‐DPMA in the food web, and especially in lake trout, may be due to obstruction of the existing carbon double bond to enzyme attack, rendering it less readily metabolized. To examine this hypothesis, biotransformation kinetic experiments using in vitro lake trout liver microsomal exposures were performed. Zero‐order depletion rate constants for 1, 3‐ and 1, 5‐DPMA were 92.2 and 134.6 pmole h−1, respectively, with corresponding half‐lives of 2.03 ± 0.14 h (1, 3‐DPMA) and 1.39 ± 0.09 h (1, 5‐DPMA). Furthermore, the 1, 5‐isomer was depleted to a greater extent than 1, 3‐DPMA. Specific biotransformation products were not identified. These data support the hypothesis that 1, 5‐DPMA is more readily metabolized than 1, 3‐DPMA by lake trout. The present study also shows that the concentrations of these isomers, which the authors speculate might be unintended impurities or byproducts in some technical DP formulations, exceed that of the intended product in biota. Environ Toxicol Chem 2013;32:1376–1381. © 2013 SETAC